Ptaquiloside from bracken (Pteridium spp.) inhibits tumour-infiltrating CD8+ T cells in HPV-16 transgenic mice. (November 2016) - Santos, Carlos; Ferreirinha, Pedro; Sousa, Hugo; Ribeiro, Joana; Bastos, Margarida M.S.M.; Neto, Tiago; Oliveira, Paula A.; Medeiros, Rui; Vilanova, Manuel; Gil da Costa, Rui M.
Abstract: Bracken is a fern with worldwide distribution. Exposure to bracken toxins such as ptaquiloside is hypothesized to increase the risk of papillomavirus-related cancers of the upper digestive tract. Ptaquiloside is thought to be an immunosupressor, thus allowing for the development of viral lesions. We have used a human papillomavirus type 16-transgenic (K14-HPV16) mouse model to study the effects of ptaquiloside on tumour-infiltrating CD8 + T lymphocytes, which are critical players in anti-tumour immunity. HPV16 +/− mice received ptaquiloside (0.5 mg/mouse/week) for 10 weeks. These were then euthanized at 30 weeks of age, along with age-matched untreated controls. Skin samples were enzymatically digested and CD8 + T cells analysed for CD107a and CD44 surface expression. Ptaquiloside-exposed HPV16 +/− mice showed a significantly decreased percentage (P < 0.05) of CD8 + CD107a + and CD8 + CD44 + T cells when compared with untreated HPV16 +/− animals. Histologically, 100% of ptaquilosidetreated mice showed diffuse epidermal dysplasia, compared with 50% of the untreated mice. These findings suggest that ptaquiloside exerts an immunosuppressive role by decreasing CD8 + T cell activation and degranulation in HPV-induced lesions. Given the key role of CD8 + T lymphocytes against HPV-induced lesions, this effect is likely to contribute for viral persistence, tumour progression and increased aggressiveness in patients with HPV-related malignancies. Highlights: Ptaquiloside is a suspect carcinogen that cooperates with papillomaviruses. Ptaquiloside impairs CD8 + T cell activation and degranulatory activity. This impairs the immune response against papillomavirus and cancer. Exposed papillomavirus-transgenic mice had enhanced epidermal dysplasia. Exposed populations may be at increased risk of papillomavirus-induced cancers.